IITA's Ronke celebrates International Youth Day 2022 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
IITA's Ronke shares her thoughts on how IITA's Start Them Early Program (STEP) has given her a voice with which she's reaching out to the youth.